Analysis of Coffee Quality and Value Chain Collaboration for a Sustainable Agro-Industry in Timor-Leste - Belo, Cecilio Alves da Costa; Henriques, Pedro Damiao de Sousa; Carvalho, Maria Leonor da Silva (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study investigates the coordination of coffee quality within the agro-commercial chain in Timor-Leste by analyzing the interaction between producers and companies engaged in production and commercialization. Coffee, as the country’s most important agricultural export and a key contributor to the non-oil economy, is internationally recognized as an organic product, with the Timor Hybrid (HDT) gaining global attention. Data were collected through documentary analysis and questionnaire surveys from 111 smallholder producers and 6 companies in Ermera Municipality, particularly in Leteffoho Administrative Post, the region with the largest plantation area and highest dependence on coffee as a source of income. The findings reveal that producers mainly cultivate Arabica and Robusta, with quality control focusing on cherry harvesting and processing, while companies predominantly purchase parchment coffee and determine prices based on quality, with only one company buying cherry coffee. All companies export green coffee, and four also sell roasted coffee in the domestic market. This study further proposes a framework that emphasizes coordination mechanisms between producers and companies to enhance quality assurance, sustain competitiveness in international markets, and strengthen the resilience of Timor-Leste’s agricultural economy.